PENGARUH KOMITMEN ORGANISASIONAL DAN JOB INSECURITY TERHADAP TURNOVER INTENTION PADA KARYAWAN ARMA MUSEUM & RESORT UBUD - Putra, Kadek Arya Ramana; Suana, I Wayan (E-Jurnal Manajemen, 2016)
Turnover intention is the desire of employees to leave the company. Turnover intention can be minimized if the company is able to give attention to the organizational commitment and the level of perceived job insecurity employees. The purpose of this study was to determine the effect organisasonal commitment and job insecurity towards employee turnover intention on Arma Museum & Resort Ubud. The sampling method using probability sampling approach, whereas the method of sampling refers slovin approach and the number of employees who qualify as a sample of 51 employees. Analysis tools using multiple linear regression techniques. The analysis shows that the commitment organisaisonal significant negative effect on turnover intention while job insecurity positive and significant effect on turnover intention. The company should always consider the level of organizational commitment and job insecurity felt by employees. It is intended that employees have a sense of security and do not have thoughts related to their desire to leave the company.
Keywords: job insecurity, organizational commitment, turnover intention